Multifunctional superhydrophobic gradient coating with ultrahigh anti-corrosion performance prepared via controlled sedimentation of nanoparticles for sulfuric acid corrosion environments - Yine Ren; Zhongqiang Yu; Wen Sun; Kaixin Xu; Junzhe Fan; Lida Wang; Zhengqing Yang; Guichang Liu; Qian Wang; Junhai Luo (Journal of Materials Research and Technology)
Simultaneously improving the corrosion protection performance and mechanical stability of coatings is a challenge in the preparation of superhydrophobic coatings. In this paper, a novel controlling sedimentation method is developed to prepare multifunctional superhydrophobic gradient coatings. The prepared gradient coating exhibits excellent superhydrophobicity with a contact angle of 156° with great chemical stability and wear resistance after the immersion of pH = 1H2SO4 and pH = 10 NaOH solution for 60 days and 180 times of sandpaper grinding. In addition, a persistent high corrosion resistance to 10 wt% H2SO4 solutions, and no cracking occurred after 240 cycles of -60 – 140 °C cold-thermal shock. This research has positive implications for the development and application of corrosion-protective organic coatings of heat exchanger equipment in the harsh environment of desulfurized flue gas, it can be applied to actual industrial production.